Stroke Prevention in Atrial Fibrillation in Older Adults: Existing Knowledge Gaps and Areas for Innovation: A Summary of an American Federation for Aging Research Seminar. Issue 10 (19th September 2013) - Lubitz, Steven A.; Bauer, Kenneth A.; Benjamin, Emelia J.; Besdine, Richard W.; Forman, Daniel E.; Gurol, Mahmut E.; Reddy, Vivek Y.; Singer, Daniel E.
<x xml:space="preserve">Abstract</x> Atrial fibrillation (AF) is a common and morbid cardiac arrhythmia that increases in prevalence with advancing age. The risk of ischemic stroke, a primary and disabling hazard of AF, also increases with advancing age. The aging of the population is anticipated to contribute to a rising burden of AF‐related morbidity and economic costs, given the close association between the arrhythmia and aging. Recent biological, diagnostic, and therapeutic developments raise hope that AF‐related stroke can be largely prevented, yet despite advances in stroke prevention for individuals with AF, numerous scientific and clinical knowledge gaps remain, particularly as these developments are applied to older adults. Given the public health importance of AF‐related stroke in elderly adults, a group of clinician‐investigators convened on April 5, 2012, to identify promising areas for investigation that may ultimately reduce stroke‐related morbidity. This article summarizes the meeting discussion and emphasizes innovative topic areas that may ultimately facilitate the application of novel preventive, diagnostic, and therapeutic insights into the management of older adults with AF. The opinions of those that participated in the meeting limit this report, which may not represent all of the questions that other experts in this field might raise.